2023
DOI: 10.1007/s11557-023-01940-2
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling intragenomic polymorphisms in the high-quality genome of Hypoxylaceae: a comprehensive study of the rDNA cistron

Marjorie Cedeño-Sanchez,
Tian Cheng,
Christopher Lambert
et al.

Abstract: Sequencing ribosomal DNA loci, such as ITS and LSU, are among the first steps to characterize and identify newly isolated fungal strains. Substantial doubt has recently been raised concerning the unequivocal suitability of using this sequence information for inferring inter- and intraspecific relationships, as especially the ITS locus was repeatedly shown to harbor high intragenomic plasticity. The evolutionary mechanisms leading to this phenomenon are poorly understood, but this is about to change, owing to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…It is worth mentioning that, because of nrDNA cistron heterogeneity, a single sequence might not be representative of the collection itself (as so well exemplified in Figure 3 and Online Resource 4a with the Amanita hiltonii ITS sequences in the outgroup (Davison and Giustiniano 2020)). Genomic analyses have demonstrated that the same can happen in the LSU (Paloi et al 2022;Cedeño-Sanchez et al 2024). Nevertheless, a recent survey has obtained a >99% pairwise identity between ITS cistrons in Amanita (Bradshaw et al 2023), therefore we feel that nrDNA cistron heterogeneity would affect, if anything, the separations at interspecies level rather than higher-level relationships.…”
Section: Discussionmentioning
confidence: 88%
“…It is worth mentioning that, because of nrDNA cistron heterogeneity, a single sequence might not be representative of the collection itself (as so well exemplified in Figure 3 and Online Resource 4a with the Amanita hiltonii ITS sequences in the outgroup (Davison and Giustiniano 2020)). Genomic analyses have demonstrated that the same can happen in the LSU (Paloi et al 2022;Cedeño-Sanchez et al 2024). Nevertheless, a recent survey has obtained a >99% pairwise identity between ITS cistrons in Amanita (Bradshaw et al 2023), therefore we feel that nrDNA cistron heterogeneity would affect, if anything, the separations at interspecies level rather than higher-level relationships.…”
Section: Discussionmentioning
confidence: 88%